Hemostatic alterations linked to body fat distribution, fatty liver, and insulin resistance - Sebastian Hörber; Rainer Lehmann; Norbert Stefan; Jürgen Machann; Andreas L. Birkenfeld; Robert Wagner; Martin Heni; Hans-Ulrich Häring; Andreas Fritsche; Andreas Peter (Elsevier, 2021)
Objective: Obesity, in particular visceral obesity, and insulin resistance emerged as major risk factors for severe coronavirus disease 2019 (COVID-19), which is strongly associated with hemostatic alterations. Because obesity and insulin resistance predispose to thrombotic diseases, we investigated the relationship between hemostatic alterations and body fat distribution in participants at risk for type 2 diabetes. Subjects: Body fat distribution (visceral and subcutaneous abdominal adipose tissue) and liver fat content of 150 participants - with impaired glucose tolerance and/or impaired fasting glucose - were determined using magnetic resonance imaging and spectroscopy. Participants underwent precise metabolic characterization and major hemostasis parameters were analyzed. Results: Procoagulant factors (FII, FVII, FVIII, and FIX) and anticoagulant proteins (antithrombin, protein C, and protein S) were significantly associated with body fat distribution. In patients with fatty liver, fibrinogen (298 mg/dl vs. 264 mg/dl, p = 0.0182), FVII (99% vs. 90%, p = 0.0049), FVIII (114% vs. 90%, p = 0.0098), protein C (124% vs. 111%, p = 0.0006), and protein S (109% vs. 89%, p < 0.0001) were higher than in controls. In contrast, antithrombin (97% vs. 102%, p = 0.0025) was higher in control patients. In multivariate analyses controlling for insulin sensitivity, body fat compartments, and genotype variants (PNPLA3I148MM/MI/TM6SF2E167kK/kE), only protein C and protein S remained significantly increased in fatty liver. Conclusions: Body fat distribution is significantly associated with alterations of procoagulant and anticoagulant parameters. Liver fat plays a key role in the regulation of protein C and protein S, suggesting a potential counteracting mechanism to the prothrombotic state in subjects with prediabetes and fatty liver.